Pengorganisasian Dalam Manajemen - Saefrudin, Saefrudin (Jurnal al Hikmah, 2017)
Humans are organizational beings. Therefore, once he was born into the world, he became a member of a genetic organization called members of a family organization. When school age, man enters school and he becomes a member of the school. After graduation and work, he became a member of the organization at his workplace. He may also be a member of a religious, youth, political, economic, and so on. Finally, after the manusa died he was recorded as a member of the organization of death by the death association committee at RT level. Thus, human beings from birth to death can not be separated from the organization. Humans are organizational beings because from birth humans can not live alone without the help of others. Organizations are formed for the benefit of humans (anthropocentric), organizations are actually created for people, not for organizations. Therefore, every day people are in touch with their organizations. Although the experience of organizing that there is a fun and annoying, there are positive and some are negative, but people still need the organization. The existence of this contradiction as a consequence that man is essentially not the same or full of differences. This difference occurs because of different educational background, experience, socioeconomic status, culture, age and so on. Not a single human being is identical, even if they are twins. Humans differ mainly from their fingerprints. What equates them is that they remain the same as humans